RECENT SEISMIC ACTIVITY IN CENTRAL GREECE REVEALING LOCAL SEISMOTECTONIC PROPERTIES - Karamanos, Ch. K.; Karakostas, V. G.; Seeber, L.; Papadimitriou, E. E.; Kilias, A.A. (Bulletin of the Geological Society of Greece, 2010)
The December 2008, M=5.2 earthquake occurred in the Voiotikos–Kifissos basin near the town of Amfikleia in Central Greece and was followed by an intense sequence with hundreds of earthquakes. Mainshock source characteristics derived from the recordings of the Greek National Seismological Network are consistent with previous known earthquakes as well as with the current nearly N–S extensional regime. The adequate azimuthal coverage and the calculated time residuals at each seismological station ensure high location accuracy, whereas the stations operated close to the seismic excitations constrained 80% of the focal depths between 8 and 12km. Distances from the mainshock epicenter to the 10 closest seismological stations vary from 15 to 75 km. Hypoinverse and HypoDD were used for locations, and FPFIT was used for fault plane solutions of events with an adequate number of clear first arrivals. The hypocenters and focal mechanisms illuminate a ≈10km–long fault zone striking nearly E–W with oblique normal faulting and a small left lateral component. The Voiotikos–Kifissos basin is bordered in the south by two left–stepping en echelon segments known as the Pavliani fault zone and the Parnassos detachment, which strike NW and dip NE. In our preferred interpretation, the Amfikleia mainshock ruptured a previously recognized south–dipping fault antithetic to the basin border faults. This fault may be associated with the left step on the border fault, which would be releasing if that fault had a sinistral component.